Sobre ocultos e indizíveis: Idosos (não vistos, mas que tudo veem) e sociabilidade um estudo naPraça Sete de Belo Horizonte - André Felipe Vieira Colares (2016)
The elderly being is different from being elder. Being elderly is a human condition that, with the passage of time brings with it the weakening of the body, limiting senses and a greater need of rest than activity. The elder self is the capital condition imposed by the labor market, looking at a person exhausted their workforce opportunities, throw it out of the market under the label of "old." Based upon the arguments of outdated, not current, limited physically and tired, capital depreciates the point of taking the old human condition and judge it in an object condition, replaceable and contemptible. In the city of Belo Horizonte, choice here to studythe space surrounding the Obelisk, called Seven Square. previously considered the ground zero of the city center, this space brings with it a weight of very great historical and social importance. This work aims to then analyze and discuss the forms of sociability of the elderly in Seven Square and social representations of this square as an area city virtualised created through speeches and experiences of the group of elderly regulars Square. Considering that it is through speech that the practice is, we need to analyze the discursive construction of SevenSquare made by these groups. After all, it is through the discourses that various representations are prepared and such representations end up interfering with the actions of the subjects. I understand then that the Seven Square is represented beyond the obelisk and its historical symbolism, hence appropriations so different. In this sense, I seek to question "what forms of sociability established by the elderly to attend Seven Square?", And it is through the general purpose of "identifying and analyzing the forms of sociability established by the elderly to attend Seven Square" this work You will be guided. About the data collectiontechniques, this work focus on capturing the social representations of the city, I had to then watch and listen to the respondents in order to capture these discourses and images that make up the city of representation for them. So I opted for three techniques: participant observation, semi-structured interview and photo-elicitation. In the data analysis, due to opt for the French discourse analysis, we seek in this work beyond the purely textual inner sphere of discourse, deepening the contextual knowledge and discussing the communication or interactionalstructures of discourse in a broader framework of relations, processes and social and political circumstances. What can be concluded is that the elderly experience in Seven Square just reinforces the difference the watchful eye of this group to the issues that surround them - unlike other people who routinely go there and are taken by an opaque cover. The elderly, the invisible them obvious. This experience of the elderly and the very search for sociability and maintaining relationships and dynamics in Seven Square already is an endless work, diverse and ample supply to think about the psychological and social construction of the basic needsof an individual. The reflections were not limited only to point out the difficulties experienced by the elderly, however rethink the old relations with himself (body and mind) with their social environment, with the structures and equipment available to them and own stimuli tolife. The elderly are much more than just a guy with age: it presents itself as a body of knowledge and wisdom, but in a low voice in the crowd.